ANALISIS KELAYAKAN USAHA DODOL RUMPUT LAUT DI UD. HARKAT MAKMUR KECAMATAN CAKRANEGARA - IDA AYU NOPIARI (Universitas Mahasaraswati K. Mataram, 2024)
One of the processed seaweeds is in the form of seaweed dodol. People's demand for seaweed dodol is increasing. The use of seaweed for dodol products can provide added value to the food. It is necessary to process seaweed products considering the high nutritional content in them. Therefore, dodol is a favorite food and is quite popular in several regions of Indonesia, including Lombok. Based on the above, research was conducted with the title